IFNL4 ss469415590 variant shows similar performance to rs12979860 as predictor of response to treatment against Hepatitis C Virus genotype 1 or 4 in Caucasians. - Luis M Real (Public Library of Science (PLoS), 2014)
Objectives The rs12979860 variant, linked to IL28B gene, predicts sustained viral response (SVR) to pegylated-interferon/ribavirin (pegIFN/RBV) therapy in Hepatitis C Virus genotype 1 or 4 (HCV-1/4)-infected patients. Recently, a functional variant, ss469415590, in linkage disequilibrium (LD) with rs12979860, has been discovered. Our objective was to assess the value of ss469415590 to predict SVR to pegIFN/RBV in Caucasian HCV-1/4-infected individuals and to compare its performance with that of rs12979860. Methods 272 Caucasian HCV-1/4-infected patients who completed a course of pegIFN/RBV were genotyped for both rs12979860 and ss469415590 markers. Logistic regression models including factors with univariate association with SVR and each genetic marker were elaborated. The area under the receiver operating-characteristic curve (AUROC) was calculated for each model and both were compared. Results Both markers were in LD (r2 = 0.82). For rs12979860, 66 (64.0%) CC versus 56 (33.1%) T allele carriers achieved SVR (Adjusted OR = 4.156, 95%CI = 2.388-7.232, p = 4.647×10-7). For ss469415590, 66 (66.0%) TT/TT versus 56 (32.5%) -G allele carriers (Adjusted OR = 4.783, 95%CI = 2.714-8.428, p = 6.153×10-8) achieved SVR. The AUROC of the model including rs12979860 was 0.742 (95%CI = 0.672-0.813) and of that based on ss469415590 was 0.756 (95%CI = 0.687-0.826) (p = 0.780). Conclusions The ss469415590 variant shows an equivalent performance to predict SVR to pegIFN/RBV than the rs2979860 in Caucasian HCV-1/4-infected patients.